Shaping US military law governing a constitutional military - Kastenberg, Joshua E. (Justice, international law and global security, 2014)
Centering on the Cold War era from 1968 onward, this book weaves judicial biography and a historic methodology into its analysis of the intersection of American military, political, social, and cultural history and the operation of the nation's armed forces.